Assessment of Tumor Burden Score as a Feasible and Reliable Tool for Prognosis Prediction for Hepatocellular Carcinoma Undergoing Hepatectomy: A Multicenter, Retrospective Study - Guan R; Zheng Z; Deng M; Mei J; Lin Y (Journal of Hepatocellular Carcinoma)
Renguo Guan,1– 4,* Zehao Zheng,2– 4,* Min Deng,5,* Jie Mei,2– 4 Ye Lin1 1Department of General Surgery, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, People’s Republic of China; 2Department of Hepatobiliary Oncology, Sun Yat-sen University Cancer Center, Guangzhou, People’s Republic of China; 3State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, Guangzhou, People’s Republic of China; 4Guangdong Provincial Clinical Research Center for Cancer, Guangzhou, People’s Republic of China; 5Department of General Surgery, The Seventh Affiliated Hospital of Sun Yat-sen University, Shenzhen, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ye Lin, Email linye@gdph.org.cn; Jie Mei, Email meijie@sysucc.org.cnBackground: Maximum diameter and number are the main parameters of tumor burden in hepatocellular carcinoma (HCC). Tumor burden score (TBS) shows its distinguished ability to stratify patients with HCC undergoing transcatheter arterial chemoembolization (TACE). However, the prognostic accuracy of TBS in HCC undergoing liver resection and its association with the BCLC stage has not been well evaluated.Methods: A total of 3044 treatment-naïve HCC patients from six independent medical centers undergoing liver resection were retrospectively analyzed. Survival analyses were conducted by plotting Kaplan–Meier curves and the Log rank test. We further investigated whether the tumor burden score was a feasible subclassification criterion across the BCLC stage. Then, we also used TBS to identify HCC patients beyond BCLC criteria who could benefit most from surgical resection. Finally, univariate and multivariate cox analysis was used to determine independent prognostic predictors.Results: About 44.2% (n=1343) of patients had low TBS, 38.8% (n=1182) had intermediate TBS and 17% (n=519) had high TBS. Overall survival (OS) and recurrence-free survival deteriorated incrementally with increasing TBS (P< 0.0001). Subgroup analysis indicated that there was a significant survival difference among the three TBS groups across the BCLC stage (P< 0.0001). Low TBS group of patients beyond BCLC criteria reported acceptable outcomes compared to intermediate TBS group patients within BCLC criteria, even better than high TBS group (5-year OS: 64.3%, 69.8%, and 56.3%). Finally, low TBS was identified as an independent protective prognostic factor.Conclusion: Tumor burden score is a feasible and reliable prognostic tool for prognosis prediction and clinical decisions.Keywords: hepatocellular carcinoma, tumor burden score, BCLC stage, prognosis prediction